2020
DOI: 10.2147/jmdh.s235930
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patients’ Experiences of a Stress-Management Programme in Primary Care</p>

Abstract: Introduction: Stress and stress-related ill health have a multifactorial impact; both on physical and mental health. To better meet this category of patients a primary care unit started a stress-management programme using cognitive behavioural therapy and basic body awareness therapy. Purpose: To describe participant´s experiences of a primary care stress-management programme using cognitive behavioural therapy and basic body awareness therapy. Methods: In a qualitative study, a semi-structured interview guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Physical activity is the most effective way to manage endocrine system and mediate stress. It has been reported that diaphragmatic breathing practice improves the cognitive performance and reduces the adverse effect of stress in healthy adults [6,[14][15][16][17]. It has been provided that effective stress management strategies such as meditation, yoga, deep breathing, which is defined as a mindfulness activity efficient for integrative body-mind training and reduces stress-related disorders, contribute to healthy lifespan, increase the quality of life, and prevent sudden death [18].…”
Section: Author Detailsmentioning
confidence: 99%
“…Physical activity is the most effective way to manage endocrine system and mediate stress. It has been reported that diaphragmatic breathing practice improves the cognitive performance and reduces the adverse effect of stress in healthy adults [6,[14][15][16][17]. It has been provided that effective stress management strategies such as meditation, yoga, deep breathing, which is defined as a mindfulness activity efficient for integrative body-mind training and reduces stress-related disorders, contribute to healthy lifespan, increase the quality of life, and prevent sudden death [18].…”
Section: Author Detailsmentioning
confidence: 99%
“…However, empirically it is well-known that preventive and rehabilitative measures take time. A qualitative study [25] of women, working or on sick leave, participating in a primary health care stress-management programme reported findings supporting that rehabilitative measures for this group warrants time. As preventive and rehabilitation measures for stressrelated ill health can take time it is possible that the effects of the RCT's preventive intervention were not visible after 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment process for brain tumors, which often involves surgery, can cause anxiety that exacerbates the stress patients are already experiencing (Ningsih et al, 2018). Prolonged stress can have a negative impact on the disease and cause depression, making it harder for the patient to cooperate with their treatment program (Köpsén & Sjöström, 2020).…”
Section: Introductionmentioning
confidence: 99%